Effect of Carburizing and Shot Peening on the Microstructure and Surface Properties of 17-CrNi6-Mo Steel - Lv, Y.H.; Gai, D.Y.; Song, Y.Q.; Ma, X.Q. (Проблемы прочности, 2015)
Carburizing and shot peening are commonly accepted surface treatment methods used to improve the surface properties of materials. Researchers are making attempts to optimize their application for obtaining superior mechanical properties. However, there are few comprehensive reports on this problem. The combination of carburizing and shot peening is used for the surface treatment of 17-CrNi6-Mo steel. This is followed by detailed analysis employing optical and scanning electron microscopy, microhardness testing, surface roughness measurements, and the measurement of residual stresses using X-ray diffraction. The results show that shot peening can further improve the microstructure and surface properties of carburized specimens since it induced the phase transformation of a carburized layer. Moreover, simulation of the phase composition variation curve along with the change in the carbon content and the continuous cooling transformation (CCT) curve of the specimen is also presented. The results are used to elucidate the carburizing effect on a 17-CrNi6-Mo steel surface microstructure. Цементация и дробеструйная обработка общепринятые методы поверхностной обработки, используемые для улучшения поверхностных свойств материалов. Ученые проводят работы в направлении оптимизации их применения с целью обеспечения высоких механических свойств. Однако существует лишь несколько подробных исследований, посвященных их применению. Комбинацию цементации и дробеструйной обработки используют для поверхностной обработки стали 17-CrNi6-Mo. После обработки проводили подробный анализ поверхности материала с использованием оптической и сканирующей электронной микроскопии, измерений ее микротвердости и шероховатости, а также остаточных напряжений с помощью рентгенографии. Результаты показывают, что дробеструйная обработка может дополнительно улучшить микроструктуру и поверхностные свойства науглероженных образцов, поскольку она вызывает фазовое превращение науглероженного слоя. Выполнено моделирование кривой вариации фазового состава с одновременным изменением содержания углерода, а также кривой превращения при непрерывном охлаждении образца. Полученные результаты используются для установления эффекта влияния цементации на микроструктуру поверхности стали 17-CrNi6-Mo.